Tooth color change promoted by different whitening toothpastes under alternate cycles of staining and brushing - Lima, Leonardo Custódio; Carvalho, Adriana Oliveira; Bezerra, Sávio José Cardoso; Garcia, Raíssa Manoel; Caneppele, Taciana Marco Ferraz [UNESP]; Borges, Alessandra Buhler [UNESP]; Scaramucci, Taís (Elsevier, 2023)
Objectives: To compare the effect of whitening toothpastes with different mechanisms of action on discolored teeth subjected to additional staining/or not. Methods: One hundred twenty tooth specimens were stained for 14 days (staining broth under constant agitation and pH=7) and then allocated into the groups of toothpastes with different whitening ingredients (n=10): 1. Regular - Colgate Total 12 Clean Mint; 2. CLWI - Colgate Luminous White Instant (blue pigment); 3. CLWA - Colgate Luminous White Advanced Expert (hydrogen peroxide); 4. CLWAC – Colgate Luminous White Activated Charcoal (activated charcoal); 5. OB3D – Oral-B 3D WHITE Brilliant Fresh (abrasive); 6. TW – Teeth Whitening (charcoal powder). Specimens were submitted to two experimental models: A. Daily staining-toothbrush cycling: staining solution (5min), toothbrushing (45 strokes) and artificial saliva (3h), 2x/day, for 5 days; B. Only toothbrushing (30.000 brushing strokes). Color change was determined with a spectrophotometer (CIEDE2000 and Whiteness Index for Dentistry - WID) and statistically analyzed (α=0.05). Results: For both models, ΔE00 and Δa did not differ significantly between the whitening toothpastes and the regular. All groups showed a decrease in tooth yellowness (-Δb) and an increase in WID. Group Teeth Whitening exhibited a decrease in luminosity (-ΔL). In model A, Groups did not differ significantly from the Regular in terms of ΔL (p=0.35) and Δb (p=0.74). Groups CLWI and OB3D exhibited a decrease in luminosity. Reduced redness (-Δa) occurred only in Group CLWI. In Model B, Groups OB3D (p=0.021) and CLWA (p=0.001) exhibited higher change in luminosity than in Group Teeth Whitening. All exhibited increased redness (+Δa) and lightness (+ΔL), except the Regular, CLWAC, and Teeth Whitening. Group OB3D had a significantly higher change in Δb than the Regular (p=0.021). Conclusions: Irrespective of the mechanism of action, all toothpastes reduced tooth yellowness and promoted similar overall color change. Exposure of the teeth to additional staining during the toothbrushing cycles did not influence the effect of the whitening toothpastes. Clinical Significance: Whitening toothpastes should be tested in conditions that more closely simulate their use in a clinical scenario, in which alternate cycles of staining and brushing occur on a daily basis. However, even in such conditions, they were unable to promote a color change that differed from that of a regular toothpaste.
Keywords: Dental abrasion; Spectrophotometer; Tooth stain; Whitening toothpastes